Optical characterization of Al- and N-polar AlN waveguides for integrated optics. (24th March 2015) - Rigler, Martin; Buh, Jože; Hoffmann, Marc P.; Kirste, Ronny; Bobea, Milena; Mita, Seiji; Gerhold, Michael D.; Collazo, Ramon; Sitar, Zlatko; Zgonik, Marko
Abstract: Dispersion of the extraordinary and ordinary refractive indices of Al- and N-polar AlN waveguides is measured by multiple angle-of-incidence and spectroscopic ellipsometry techniques. The polarity-controlled AlN layers are grown by metal–organic chemical vapor deposition on (0001)-sapphire substrates. Taking into consideration the different surface morphologies of the Al- and N-polar AlN waveguides, we propose two optical models to describe the measured ellipsometry data. The results indicate that there is no difference between the refractive indices of the AlN grown in opposite directions, which confirms the potential of the AlN lateral polar structures for use in nonlinear optical applications based on quasi phase matching.